Two Types of the East Asian Cold Surge and Their Impacts on El Niño. Issue 3 (7th February 2022) - Feng, Jie; Lian, Tao; Ding, Yihui; Li, Xichen; Sun, Cheng; Chen, Dake
Abstract: Case studies have shown that the East Asian cold surge (CS) in winter exerts considerable impact on the development of El Niño by changing the surface wind over the western equatorial Pacific. However, a statistical assessment of the conditions under which the CS is more likely to make such an impact is lacking. Our statistical analysis shows that the CS can be divided into two types with respect to their prevailing area. The western CS type passing through the South China Sea rarely influences the equatorial surface wind owing to blocking and friction effects from high mountains in Borneo, whereas the eastern CS type passing through the Philippine Sea induces strong equatorial surface westerly anomalies. Observations and model experiments show that only the eastern CS type can efficiently trigger El Niño. Plain Language Summary: Equatorial surface wind changes are important for the development of El Niño. Previous case studies have indicated that the East Asian cold surge (CS) can change the surface wind over the western equatorial Pacific, but a statistical assessment of the conditions under which the CS is more likely to make such an impact is lacking. By dividing the CS into two types, we found that the western CS type passing through the South China Sea rarely influences the equatorial Pacific. In contrast, the eastern CS type passing through the Philippine Sea induces significant surface westerly anomalies that account for the majority of westerly anomalies during the onset phase of El Niño. Coupled model experiments also support the role of the eastern CS type dynamically. Key Points: The East Asian cold surge can be classified into western and eastern types The impacts of the two types on equatorial zonal wind are different Only the eastern type favors El Niño onset via increasing equatorial westerly anomalies